Anthropogenic carbon inventory in the Gulf of Cádiz - Flecha, Susana; Pérez, Fiz F.; Navarro, Gabriel; Ruiz Segura, Javier; Livé, I.; Rodríguez-Gálvez, Susana; Costas, Eduardo; Huertas, I. Emma (Journal of Marine Systems, 2012)
9 páginas, 2 tablas, 6 figuras.-- Proyecto Carbochange The North Atlantic is the most important sink for atmospheric CO2 although there still remain uncertainties about the total amount stored by this region and the contribution of the anthropogenic CO2 (CANT) that is exchanged between the Mediterranean Sea and the Atlantic Ocean. During the P3A2 cruise performed in October 2008 throughout the oceanic area covered by the Gulf of Cádiz and the Strait of Gibraltar, which channelizes the water exchange between the Atlantic and the Mediterranean, extensive measurements of the carbon system parameters (pH, total alkalinity and total inorganic carbon) and others related (dissolved oxygen and nutrients) were carried out to analyze their distribution in the area. In order to study the CANT spatial variability, three observational methods for CANT concentration assessment (φCT°, ∆C* and TrOCA) were applied. The three water masses identified in the area, North Atlantic Central Water (NACW), North Atlantic Deep Water (NADW) and Mediterranean Outflow Water (MOW), were shown to contain different CANT concentration. NADW exhibited the lowest CANT levels whereas NACW was the most CANT enriched. Data also indicate a net import of CANT from the Atlantic towards the Mediterranean through Gibraltar. Specific CANT inventories showed that MOW contributes in 8–12% to the total specific CANT inventory of the Gulf of Cádiz. Funding for this work was provided by the European Projects CARBOOCEAN IP(511176GOCE) and CARBOCHANGE(264879) and by the Spanish Ministry of Sciences and Innovation through the projects and . Peer reviewed